(untitled) (Nonconventional Technologies Review, 2025)
This study presents the modeling and simulation of a biped walking robot using MathWorks® simulation tools. The project focuses on developing a parametric and dynamic model that accurately represents the mechanical structure, joint kinematics, and actuator behavior of a bipedal robot. The methodology involves 3D modeling of the robot’s components, simulation of foot–ground contact forces, and comparative analysis of different actuation strategies—motion-based, torque-driven, and motor-based systems. By integrating mechanical, electrical, and control subsystems, the study evaluates trade-offs between model fidelity and simulation speed. Results indicate that while motor-actuated models provide higher physical realism, they significantly increase computational complexity. The work also highlights the importance of appropriate damping, force modeling, and control architecture (PID) for ensuring stable gait dynamics. Future developments include hardware implementation, enhanced actuator modeling, and machine learning approaches for optimizing walking performance.